2014 European Conference on Networks and Communications (EuCNC) 2014
DOI: 10.1109/eucnc.2014.6882618
|View full text |Cite
|
Sign up to set email alerts
|

3G access network dimensioning in isolated rural areas based on femtocells

Abstract: Based on the definition of the access network architecture and the forecast of voice and data traffic evolution, this paper derives engineering rules for radio network dimensioning of 3G femtocell-based access networks in isolated rural areas. Network dimensioning exercise focuses not only on the access network, but also on the necessary backhaul bandwidth and the required number of solar energy power supply units. Different femtocell-based deployments have been studied, whose appropriateness is related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This paper generalizes two previous works by us [1,2]. In particular, the differences introduced in this paper are the following: we generalize the mathematical analysis by considering a more complex scenario (two possible configurations), we present a more rigorous energy dimensioning, we develop more complete simulations, and for the on/off switching strategies, we generalize [2] by considering that we have two different types of traffic.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…This paper generalizes two previous works by us [1,2]. In particular, the differences introduced in this paper are the following: we generalize the mathematical analysis by considering a more complex scenario (two possible configurations), we present a more rigorous energy dimensioning, we develop more complete simulations, and for the on/off switching strategies, we generalize [2] by considering that we have two different types of traffic.…”
Section: Introductionmentioning
confidence: 68%
“…The difficult access to these areas, the high cost derived from the required network equipment and the deployment of the backhaul, and the low density of subscribers are the main factors resulting in low-profit business. On the other hand, recent experiences in rural South America and Africa have shown that the access to Internet and to mobile voice services are key *Correspondence: jaume.delolmo@tsc.upc.edu Partial results of this paper have been presented previously by the same authors in conferences EUCNC 2014 and IEEE SPAWC 2014 (©2014 IEEE: some materials are reprinted, with permission, from [1] and [2]). Department of Signal Theory and Communications, Universitat Politècnica de Catalunya (UPC), Jordi Girona 1-3, Building D5, 08034 Barcelona, Spain factors for the improvement of the economy and life standards in terms of social services, education or health care programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation